What’s Modern in Chinese Translation Theory? Lu Xun and the Debates on Literalism and Foreignization in the May Fourth Period - Tak-hung Chan, Leo (TTR)

(untitled) (Association canadienne de traductologie, 2001)
AbstractThis article attempts to assess the contribution of Chinese translators and theorists of the twenties and thirties, in particular the famous writer Lu Xun, whom I consider the first modern translation theorist in China. It is with him that China entered its modern phase in translation. Not only did he advocate retaining the foreignness of the original text, in a way reminiscent of the entire tradition of German Romantic translation theorists from Schleiermacher to von Humboldt to Goethe; he also explored in his own translations the possibilities for enriching the Chinese language through the importation of Europeanized structures and expressions. It is these foreignizing impulses that set Lu Xun apart most clearly from pre-modern Chinese theorists. At the same time, these impulses connect him with leading giants of translation theory like Nabokov and Benjamin (who emphasized the importance of the literal method in translation) on the one hand, and Venuti and Holmes (who highlighted processes of indigenization and exoticization in translation) on the other.Lu Xun’s ideas had a particular place in the wider cultural and historical context. Views similar to his had been advocated by his predecessors at the beginning of the century, whose attempt to Europeanize the classical language did not, unfortunately, find a large following. In his own time, Lu found ardent supporters among friends and colleagues who either (a) suggested thorough Europeanization, or (b) preferred limited Europeanization. Dissenting views, however, were clearly voiced by some of the other leading writers of the day. So there were (a) those who favored the use of a language based on the actual words spoken by the populace and (b) those who queried why one should not learn a foreign language and read the original instead. My article deals at length with the debates among these theorists and seeks to understand them from the perspective of contemporary Western translation theory.